A, The classroom research Upaya Meningkatkan Ketrampilan Menulis Teks Prosedur bagi Peserta Didik Kelas XII DPIB dengan Menggunakan Media Pemanfaatan Bekas Bungkus Kemasan pada Semester Genap Tahun pelajaran 2021/2022: - - hartatik, agus (JURNAL ILMIAH UNSTAR ROTE, 2024)
Students think that studying English is very difficult, so it make them feeling lazy to explore their skills and competence. The shadow to some difficulties to change their mindset, it is so hard. When the teacher gives the topic about Procedure Text, they have same condition. Not motivation, no spirit, and no desire to change. The writer wants give other solution to make them motivated have spirit, and full desire. The writer uses one media, as The usage of product packaging. The research does classroom research.In cycle 0ne, the grade of students have under the criteria minimum. From 39 students, there are 30 students do not pass from the minimum criteria. In cycle two, by using product packaging, the students pass from the minimum criteria. They get good score in writing procedure text.